2015
DOI: 10.1675/063.038.0409
|View full text |Cite
|
Sign up to set email alerts
|

Density Dependent Double Brooding in Piping Plovers (Charadrius melodus) in the Norhern Great Plains, USA

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Though not carryover effects, these compensation effects are seasonal interactions and may interact with individual carryover effects in complex ways (Harrison et al, 2011). Density is an important determinant of reproductive output for plovers in our population (Catlin et al, 2014;Hunt, 2016;Hunt et al, 2015), and it may affect other factors in their life cycle. These seasonal compensation effects, however, are positively correlated with the level of migratory connectivity or geographic linkage among populations (Norris & Marra, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Though not carryover effects, these compensation effects are seasonal interactions and may interact with individual carryover effects in complex ways (Harrison et al, 2011). Density is an important determinant of reproductive output for plovers in our population (Catlin et al, 2014;Hunt, 2016;Hunt et al, 2015), and it may affect other factors in their life cycle. These seasonal compensation effects, however, are positively correlated with the level of migratory connectivity or geographic linkage among populations (Norris & Marra, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Non-breeding female plovers, however, would presumably not have a territory and thus would be more mobile. distance traveled between consecutive years and nests for plovers in this population was 153 m (Friedrich et al 2015). Many studies have affirmed the fidelity of plovers to locations across the annual cycle; fidelity of breeding birds to their populations (variously defined) across several studies was ≥83% and ≥46% for returning hatch year birds and appears to be relatively high for wintering birds as well (Gratto-Trevor et al 2016, Gibson et al 2018.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have indicated that reproductive output (chick survival), site fidelity, and immigration rates are also density dependent in this population , Hunt et al 2015, 2018. Moreover, these birds were indirectly affected by density because at higher nest densities, fewer plovers bred, and non-breeding plovers had lower survival.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations